2015
DOI: 10.2754/avb201584030269
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selected feed supplements on the growth and health of calves depending on the sex, season of birth, and number of the dam’s lactations

Abstract: The aim of this study was to prove the hypothesis that the growth and health of calves are dependent on feed supplements with an antidiarrhoeic effect, in relation to sex, season of birth, and number of the dam's lactations. A total of 186 calves were included in the experiment. After birth the calves were divided into three treatment groups: Ascophyllum nodosum (brown seaweed hydrolyzate, prebiotics), Lactobacillus sporogenes (probiotics), and the control group. All calves were weighed within two h after birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The age of weaning was higher in primiparous dams than other groups, but the differences did not reach the significance. The decrease of birth weight in primiparous cows reflected increase the age of weaning, as shown Zábranský et al (2015) who cited that calves from primiparous dams showed significantly lower live body weights at birth, also at the last weighing on day 28 compared to calves from older cows. The growth rate, as shown in table (6) was significantly affected by lactation season, where it was the highest in 2 nd season (Dhakal et al, 2013).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The age of weaning was higher in primiparous dams than other groups, but the differences did not reach the significance. The decrease of birth weight in primiparous cows reflected increase the age of weaning, as shown Zábranský et al (2015) who cited that calves from primiparous dams showed significantly lower live body weights at birth, also at the last weighing on day 28 compared to calves from older cows. The growth rate, as shown in table (6) was significantly affected by lactation season, where it was the highest in 2 nd season (Dhakal et al, 2013).…”
Section: Resultsmentioning
confidence: 85%
“…Calves received fresh colostrum collected from their dam as soon as possible after birth (within 1 hour) with an average amount of 2 liters then increased to 8 liters within the first 24 hours. Calves fed milk ad libitum by artificial teat with a plastic bottle that was fitted in front of the hutches at a height of 40 cm above the ground during the experimental period (Zábranský et al, 2015). All calves are fed whole milk mixed with non-saleable milk after pasteurization.…”
Section: Animals Used and Managementmentioning
confidence: 99%
“…Zdravý střevní mikrobiom zajišťuje optimální trávení a efektivní vstřebávání živin, čímž podporuje růst a zlepšuje účinnost krmiva u hospodářských zvířat (Kumar et al, 2016;Ugbogu et al, 2019). To je dnes řešeno používáním probiotik ke zlepšení růstové výkonosti zvířat, což se jeví jako úspěšné (Zábranský et al, 2015;Zábranský et al, 2021).…”
Section: Podpora Růstu a Využitelnost Krmivaunclassified
“…Calving ease is often analyzed in cattle in relation to other important parameters. For example, the mother's nutritional status and body condition score also influence calving ease (Zabransky et al, 2015). Calving ease is mentioned very often in beef breeds of cattle; for example, a study on the Belgian Blue breed looked at the internal dimensions of the pelvis and their influence on the difficulty of calving (Coopman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%